The Effect Of Production Costs and Sales Volume (Nett) On Nett Profit In Manufacturing Companies In The Primary Consumer Goods Sector Listed On The Indonesia Stock Exchange For The 2017-2021 Period - Ratna Ningsih; Mochamad Zakaria; Maria Lusiana Yulianti (DINASTI RESEARCH, 2022)
The purpose of this research are to analyze: 1) to test the effect of production costs on nett profit; 2) to test the effect of sales volume (nett) on nett profit; 3) to test the effect of production cost and sales volume (nett) on nett profit in manufacturing companies in the primary consumer goods sector for the 2017-2021 period. The populations in this research is manufacturing companies in the primary consumer goods sector for the 2017-2021 period. The technique used in selecting the sample was purposive sampling and obtained 44 manufacturing companies in the primary consumer goods sector with a research periode of 5 five years so that 220 samples were obtained in this research. The data analysis method in this research was panel data regression analysis using Eviews software version 10. The results of this research indicate that: 1) production costs have a positive and significant effect on nett profit; 2) sales volume (nett) has a positive and significant effect on nett profit; 3) it is then known that there is a jointly significant effect between the variables of production costsand sales volume (nett) to nett profit in manufacturing companies in the primary consumer goods sector for the 2017-2021 period.